The threat to Israel’s identity in Deuteronomy: Mesopotamian or Levantine? - Crouch, C.L. (De Gruyter, 2012)
Deuteronomy contains a number of indications which locate its interests in the Levant rather than in Mesopotamia. This observation challenges two major theories of the book’s origins: Deuteronomy as pre-exilic attempt to subvert Assyrian imperial power and Deuteronomy as exilic, utopian manifesto for a restored Israel. The indications of a true Levantine context for the deuteronomic interest are identified in both the legal content of the book (passages which presuppose the audience’s presence in the land or identify its interests with the southern Levant and its inhabitants) and in its terminology (»in/from your midst«, »other gods«, lack of »foreigner« language). Note is also made of later attempts to reapply material originally orientated toward the Levant to an exilic population dealing with Mesopotamian culture.